The Mystics: A Novel - Thurston, Katherine Cecil, 1875-1911 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Mystics: A Novel" by Katherine Cecil Thurston is a fictional work written in the early 20th century. The story unfolds around the lives of John Henderson and his dying uncle, Andrew Henderson, who is part of a secretive religious sect known as the Mystics. As John navigates the complexities of his heritage and the emotional weight of watching his uncle pass away, the themes of familial obligation, ambition, and the search for meaning in life begin to emerge. The opening of the novel introduces us to John Henderson, a young man in a tense vigil as his uncle lies dying in a remote Scottish house. The atmosphere is charged with the looming presence of death, and John's emotions are a mixture of grief and an unexpected sense of liberation$1 (Bhe has long suffered under his uncle's oppressive rule. As the narrative unfolds, John's curiosity about his uncle's mysterious beliefs grows, especially when he learns of a secret book that holds the promise of power and enlightenment within the sect. The opening chapters highlight themes of promise and disillusionment while foreshadowing the power struggle and internal conflicts that will guide John's journey of self-discovery in the quest for true identity and purpose. (This is an automatically generated summary.)s
Release date is 2007-04-17
E-text prepared by Suzanne Shell, Storm, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Inheritance and succession -- Fiction; Impostors and imposture -- Fiction; Uncles -- Fiction; Man-woman relationships -- Fiction; Cults -- Fiction